The Effect of Counterpressure Techniques on Decline Labor Pain in Maternity During Active Phase I Hospital I.A. Moeis - Jens Verty Lebang; Jasmawati; Rivan Firdaus (Formosa Journal of Applied Sciences, 2023)
According to data from the World Health Organization (WHO), the average standard for Sectio Caesare in a country in the world is 10 to 15% and Sectio Caesare, especially in developing countries (Sa'diyah, 2020). The purpose of this study was to find out whether there is an increase in technical influence in the following year, around 22.5% of deliveries in the world are carried out with counterpressure measures to reduce labor pain in active phase I labor mothers at I.A. Hospital. Moeis. This type of research is Quasy Experiment with a two-group pretest posttest design. Results Testing the hypothesis with paired t test found that there is an effect of counterpressure technique with a p-vlaue of 0.000 on decreasing the scale of labor pain at I.A Moeis Hospital Samarinda. There is an effect of counterpressure technique on decreasing labor pain in labor during the first active phase at the I.A Moeis Hospital in Samarinda.